PEMAHAMAN PESERTA PADA PROGRAM MODEL KAWASAN RUMAH PANGAN LESTARI (MKRPL) (Kasus pada peserta program MKRPL di Desa Singamerta) - Irfan Setiawan; Asih Mulyaningsih; Ari Tresna Sumantri (JURNAL AGRIBISNIS TERPADU, 2015)
Model Kawasan Rumah Pangan Lestari (M-KRPL) is an empowerment program for people inIndonesia. There need good comprehension from the participants to realize the goals of theempowerment program. The main purpose of this research is to analyze the comprehension of MKRPLparticipants in Singamerta. Respondents of this research were taken by census method withaggregate as much as 39 respondents. To measure the comprehension of M-KRPL participants is bygiving interview test including purpose, goal and limitation of program M-KRPL. This research useddescriptive analysis with making cross-tabulation. The census results showed that most of M-KRPLparticipants in Singamerta are productive women. Characteristic according to education, most of MKRPLparticipants just graduated elementary school by percentage as much as 61.54 percent.Characteristic according to main job, most of M-KRPL participants are homemakers even the rest asmuch as 25.64 percent are trading. M-KRPL participants in Singamerta have differentcomprehensions including purpose, goal and limitation. Most of M-KRPL participants in Singamertahave good comprehensions. It was showed by the percentage as much as 58.97 percent for purposeand goal, even 61.54 percent for limitation.